Effects of Macroeconomics Factors toward Efficiency in Banking - Fakhrunnas, Faaza; Nahar, Faiza Husnayeni; Albana, Hilman Fikri (Universitas Negeri Semarang, 2018)
The main objective of this study is to analyze the effect of macroeconomic factors toward efficiency in Islamic and Conventional Banking. Banking as one of components in financial system that highly contributes to the growth and development of the economy in a country, especially after establishment of the first Islamic bank in Indonesia at the year of 1992. Afterwards, Islamic banking began to develop and start to compete with conventional banking. Hence, in order to survive and do fair competitiveness, Islamic and Conventional banking have to maintain its efficiency. This study uses the methodology of Data Envelopment Analysis (DEA). This study also analyze the macroeconomics factors namely inflation, interest rate of Bank indonesia and the growth of Gross Domestic Product (GDP) which affects the bank efficiency. Our data is obtained from annual financial statement published by each islamic and conventional bank and Bank Indonesia starting from 2007 to 2016. This study shows that conventional banks have higher efficiency than Islamic banks, while crisis in 2008 had no significant effect on the efficiency of Islamic and conventional banking. However, a decrease in the level of efficiency that occurs in conventional banking indicates that conventional banking is more sensitive to the crisis.